Investigating Motivational Factors: Riba Avoidance, Religiosity, Reputation, Social Environment, and Sharia Bank Product Adoption - Fauziah, Nurlaily; Amri, Muhtadin (Etihad: Journal of Islamic Banking and Finance, 2023)
Introduction: This study aims to examine and analyze the influence of the motivation to avoid riba, religiosity, reputation and social environment of Al-Islam Islamic Boarding School alumni Joresan Mlarak Ponorogo on the decision to use Islamic banking products. Research Methods: This study used a quantitative approach with data collection techniques using questionnaires to 97 respondents. The sampling technique used snowball sampling and data analysis techniques using multiple linear regression. Results: The results indicates that the motivation to avoid riba, religiosity, reputation and social environment have an effect on the decision to use Islamic bank products. Conclusion: This   findings highlights the importance of Islamic Banking to considering the motivation to avoid riba, religiosity, reputation and social environment by individuals to make decisions regarding their banking choices.